2012
DOI: 10.1111/j.1600-0706.2012.20655.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal, not annual precipitation drives community productivity across ecosystems

Abstract: Understanding drivers of aboveground net primary production (ANPP) has long been a goal of ecology. Decades of investigation have shown total annual precipitation to be an important determinant of ANPP within and across ecosystems. Recently a few studies at individual sites have shown precipitation during specific seasons of the year can more effectively predict ANPP. Here we determined whether seasonal or total precipitation better predicted ANPP across a range of terrestrial ecosystems, from deserts to fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 64 publications
7
94
3
1
Order By: Relevance
“…At the ecosystem scale, variation in global plant productivity across ecosystems has often been related to environmental factors (Field et al 1995, Reichstein et al 2007b), but also to nutrient availability (Vicca et al 2012). In this context, Zha et al (2013) reported a strong positive relationship between GPP or NPP and total soil N. Across our sites, ΔCwood and ANPP increased slightly, but not significantly with increasing soil C:N, and showed significant relations with MAT, MAP and stand age, thus confirming previous studies (Curtis et al 2002, Hsu et al 2012, Robinson et al 2012, He et al 2012). How such different behavior between GPP and ΔCwood or ANPP with respect to soil C:N could be explained?…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At the ecosystem scale, variation in global plant productivity across ecosystems has often been related to environmental factors (Field et al 1995, Reichstein et al 2007b), but also to nutrient availability (Vicca et al 2012). In this context, Zha et al (2013) reported a strong positive relationship between GPP or NPP and total soil N. Across our sites, ΔCwood and ANPP increased slightly, but not significantly with increasing soil C:N, and showed significant relations with MAT, MAP and stand age, thus confirming previous studies (Curtis et al 2002, Hsu et al 2012, Robinson et al 2012, He et al 2012). How such different behavior between GPP and ΔCwood or ANPP with respect to soil C:N could be explained?…”
Section: Discussionsupporting
confidence: 88%
“…Several factors may, however, influence the magnitude and direction of the net C balance, including recovery from historical land use (e.g., abandoned agricultural land reverting to forested land), increases in atmospheric CO2 concentration and nitrogen (N) deposition, and climate change (Schimel et al 2001, Thomas et al 2010. Nonetheless, while much research has been done to understand the controls on net ecosystem C balance (Valentini et al 2000, Rustad et al 2001, Reichstein et al 2007a), we know little about the controls on C sink partitioning between plant biomass and soil organic matter (SOM) pools. Soils may store C for long periods of time (Lal 2005), accumulating on average three times the C in terrestrial vegetation (Post et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…5b) and 32% of annul GPP (p = 0.05). To some extent this supports how the timing of growing season onset (Lafleur and Humphreys, 2007;Shen et al, 2011) and soil water status can play a positive role in vegetation activity in alpine grassland ecosystems (Robinson et al, 2013;Shen et al, 2015b).…”
Section: Inter-annual Variations Of Gpp Res and Neementioning
confidence: 96%
“…According to the phenology of most of flora in alpine shrublands, the growing season (from a flux data processing perspective) is defined as April 20-October 10 . Meanwhile, based on a plant-centric year rather than the calendar year (Robinson et al, 2013;Li et al, 2015), last October 11-April 19 is classified as the non-growing season of the current year. However, the non-growing season in 2003 only covered January 1-April 19 due to a lack of data.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Furthermore, in some dry climates where rainfall and potential evapotranspiration are in-phase, annual evapotranspiration can be shown to increase because of inter-seasonal soil moisture transfer, highlighting the importance of soil water storage in the seasonal context. plant responses and adaptive strategies [3,4], regional vegetation distribution, carbon fluxes and primary productivity [5][6][7][8], with further implications for agriculture and land management [9]. These scientific emphases on the role of climate seasonality come at a time of discernible climate change.…”
mentioning
confidence: 99%